A systematic review on costs and cost-effectiveness of screening and prevention of type 2 diabetes in women with prior gestational diabetes: Exploring uncharted territory. (January 2019) - Werbrouck, Amber; Schmidt, Masja; Putman, Koen; Benhalima, Katrien; Verhaeghe, Nick; Annemans, Lieven; Simoens, Steven
Abstract: Aims: Women with gestational diabetes mellitus (GDM) are more likely to develop type 2 diabetes mellitus (T2DM) as compared to women with normoglycemic pregnancies. This study aims to explore the literature on cost(-effectiveness) of screening and prevention of T2DM in women with prior GDM. Methods: Five databases were systematically searched, inclusion criteria were: (1) women with (prior) GDM; (2) post-partum screening or prevention of T2DM; and (3) health-economic evaluations. No year limits were applied. English, Dutch, French or German publications were included. Quality was assessed using the Consensus Health Economic Criteria checklist. Results: Two cost-effectiveness analyses and two cost analyses were found. One study evaluated nine screening strategies. Three studies evaluated one prevention strategy each: intensive diet and behavioural modification; annual counseling; and an annual dietary consultation. Methodological quality was poor. Perspectives were unclear, time horizons were too short, and no incremental analyses were performed. Conclusion: An oral glucose tolerance test per three years leads to the lowest cost per case detected, and prevention is potentially cost-effective or cost-saving. More health economic evaluations are needed that compare all relevant alternatives, including 'doing nothing'.